Case Report: The Neuromusclar Triad of Immune Checkpoint Inhibitors: A Case Report of Myositis, Myocarditis, and Myasthenia Gravis Overlap Following Toripalimab Treatment - Luo, Yue-Bei; Tang, Weiting; Zeng, Qiuming; Duan, Weiwei; Li, Shuyu; Yang, Xiaosu; Bi, Fangfang (Frontiers in Cardiovascular Medicine, 2021)
The neuromuscular adverse events of immune checkpoint inhibitor (ICI) treatment include myositis, polymyalgia rheumatica, myocarditis and myasthenia syndrome. We report a 47-year old female presenting with external ophthalmoplegia, generalized muscle weakness and third degree atrioventricular block four weeks after Toripalimab treatment for metastatic thymoma. Creatine kinase was elevated to 25,200U/L and cardiac troponin I to 2.796ng/ml. Autoantibody profiling shows positive anti-ryanodine receptor and anti-acetylcholine receptor antibodies and negative myositis specific antibodies. Repeated nerve stimulation did not reveal decrement of compound muscle action potentials. Pulse methylprednisolone and immunoglobulin infusion, together with temporary pacemaker insertion normalized her muscle enzyme levels and cardiac rhythm. This is the first report of neuromuscular adverse event of Toripalimab.